Response of polymers and nutrient management on growth, yield, and quality of Indian mustard (Brassica juncea) - MEENA, RAM SWAROOP; PATEL, DIVYA; DE, NIRMAL; SINGH, AJEET; GURJAR, D S; KUMAR, SUNIL; PRADHAN, GOURISANKAR (The Indian Journal of Agricultural Sciences, 2020)
..